Reproductive Rights in the Context Of Medical Law and Demograpic Trends - Mujović, Hajrija; Šobot, Ankica (Medicine, Law & Society, 2024)
Medical Law examines reproductive rights through the prism of reproductive health. It encompasses all aspects from the perspective of human rights. The focus is on sources of law. The medical context of issues is very important. It is considered a serious violation if basic rules such as informed consent and patients' rights are neglected. Considering demographic trends leads to a connection between birth rates and restrictive legislation which has not been confirmed as a good solution. The conclusion emphasizes that medical law should have a more contributing role in improvement of reproductive health services, quality standards, and better legal perception and protection for all.